Tari Ngibing Ngalegong: Sebuah Ungkapan Rasa Suka Cita, Tulus, dan Ikhlas - Ni Kadek Prastya Maharani; Gusti Ayu Ketut Suandewi; I Wayan Adi Gunarta (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
The dance piece titled Ngibing Ngalegong is inspired by one of the sections of the legong dance originating from the village of Bongan in Tabanan. Ngibing Ngalegong is a creative palegongan dance piece that highlights the ibing-ibingan movements at the end of the Joged Bisama Legong Keraton dance. In this piece, the ibing-ibingan movements are made more structured and feature harmonious paired patterns. Ngibing Ngalegong comes from two words, ngibing and ngalegong. The word ngibing is taken from the final part of the Joged Bisama Legong Keraton dance, namely ibing-ibingan, which is simplified to ngibing. Meanwhile, ngalegong comes from the word legong, to which the choreographer added the prefix nga, meaning packaged into palegongan. In the creation of the Ngibing Ngalegong dance, the method used is based on the Angripta Sasolahan method (creating dances). This creation method includes five important stages: ngarencana (the preparation or planning stage for creating the work), nuasen (the ritual or spiritual stage to begin the creation process), makalin (the selection of materials needed for creation), nelesin (the formation stage to harmonize and perfect the work), and ngebah (the premiere performance of the complete dance work). The Ngibing Ngalegong dance has a social-religious theme. The ngibing interaction can be described as social and religious because the Legong Bisama ngibing is believed to ward off evil. The Ngibing Ngalegong dance is performed in a group using six female dancers. The stage makeup used in the Ngibing Ngalegong dance follows Balinese dance stage makeup, while the costumes are based on the general Legong dance costumes but with more developed designs and shapes, incorporating cream-colored elements. The Ngibing Ngalegong dance uses a Musical Instrument Digital Interface (MIDI) application as its accompanying music, featuring a 12-minute sample of the Semarandhana gamelan. Keywords: Ngibing Ngalegong, Ibing-ibingan, Creative Palegongan